2020
DOI: 10.1128/jvi.01151-20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Escape Mutant-Specific T Cells in Suppression of HIV-1 Replication and Coevolution with HIV-1

Abstract: The accumulation of HIV-1 escape mutations affects HIV-1 control by HIV-1-specific T cells. Some of these mutations can elicit escape mutant-specific T-cells, but it still remains unclear whether they can suppress the replication of HIV-1 mutant viruses. It is known that HLA-B*52:01-restricted RI8 (Gag 275-282, RMYSPTSI) is a protective T cell epitope in HIV-1 subtype B-infected Japanese individuals, though 3 Gag280A/S/V mutations are found in 26% of them. Gag280S and Gag280A were HLA-B*52:01-associated mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…4B and Table 2 ). The viral suppression ability of these primed T-cell lines was evaluated by comparing it with that of a positive-control CTL clone, 12B (GagRI8-specific), D3 (PolSI8-specific), or C5 (GagWV8-specific), which showed a very strong viral suppression ability in vitro ( 27 , 34 ). Most of the primed T-cell lines specific for GagRI8, GagWV8, or PolSI8 epitopes exhibited high viral suppression ability, which was approximately 80% of that of the positive-control clone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4B and Table 2 ). The viral suppression ability of these primed T-cell lines was evaluated by comparing it with that of a positive-control CTL clone, 12B (GagRI8-specific), D3 (PolSI8-specific), or C5 (GagWV8-specific), which showed a very strong viral suppression ability in vitro ( 27 , 34 ). Most of the primed T-cell lines specific for GagRI8, GagWV8, or PolSI8 epitopes exhibited high viral suppression ability, which was approximately 80% of that of the positive-control clone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each well contained 200 μl of cell mixture (1 × 10 5 irradiated allogeneic PBMCs from healthy donors and 1 × 10 5 irradiated C1R-B*52:01 cells prepulsed with the peptide at 100 nM, 20 ng/ml of human recombinant interleukin 2 (rIL-2; ProSpec), and 2.5% phytohemagglutinin soup). CTL clones specific for HLA-B*52:01-restricted GagRI8, GagWV8, or PolSI8 were established from HIV-1-infected individuals as previously described ( 27 , 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, an association between the level of CD8 + T-cell polyfunctionality and the peptide-HLA-I binding affinity was observed; specifically, higher CD8 + T-cell polyfunctionality was found in response to the S54T peptide compared to S54A/E55G peptide, associated with lower HLA-I binding affinity. Some studies have shown that changes at the central position of an epitope may alter its recognition by the T cell receptor (TCR) ( 47 , 48 ) and that the level of polyfunctionality is influenced by the affinity of the TCR-pMHC interaction ( 49 ). Thus, our findings suggest that position six is a relevant site for epitope recognition and that the change from a serine to a threonine may contribute to the avidity of the TCR-pMHC complex.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that three HLA alleles, HLA-B*67:01, HLA-B*52:01, and HLA-C*12:02, were significantly associated with both low pVL and a high CD4 count in HIV-1 subtype B-infected Japanese individuals, indicating that these three HLA alleles have a protective effect on HIV-1-infected Japanese individuals ( 8 ). Furthermore, it has been demonstrated that the epitope-specific CD8 + T cells restricted by these three protective HLA alleles effectively suppressed HIV-1 replication in Japanese individuals ( 24 26 ).…”
Section: Introductionmentioning
confidence: 99%